e Timoshenko Three-Beams Technique To Estimate The Main Elastic Moduli Of Orthotropic Homogeneous Materials - Saify, Kamal K.M.; Al-Temimy, Adnan N.J.; J.J, Muhsin (Al-Khwarizmi Engineering Journal, 2017)
A New developed technique to estimate the necessary six elastic constants of homogeneous laminate of special orthotropic properties are presented in this paper for the first time. The new approach utilizes the elasto-static deflection behavior of composite cantilever beam employing the famous theory of Timoshenko. Three extracted strips of the composite plate are tested for measuring the bending deflection at two locations. Each strip is associated to a preferred principal axis and the deflection is measured in two orthogonal planes of the beam domain. A total of five trails of testing is accomplished and the numerical results of the stiffness coefficients are evaluated correctly under the contribution of the macromechanics and the approximate bending theory. To insure the validity of the new approach, separate individual tensile tests are performed, and the corresponding results are compared. Excellent agreements are obtained between the different approaches. The ease, simple and accurate predictions are well confident by the new technique.